Antenatal sonographic features of persistent extrahepatic vitelline vein aneurysm confused with umbilical vein varix. (2nd November 2019) - Chae, Song-Hwa; Ji, Il Woon; Hong, Seung Hwa; Choi, Jin Young; Lee, Ho-chang; Kim, Jung-Sun; Kim, Bitna; Kim, Ji-Hun; Song, KiHyeok
Abstract: Background: The persistent vitelline vein is a portal venous system malformation arising during the embryonic period. These abnormal blood vessels frequently thrombose and can lead superior mesenteric vein obstruction or portal hypertension. Case report: We visualized a fetal intra-abdominal cystic mass with turbulent flow on prenatal ultrasound at 28 weeks' gestation. Initially diagnosed as an umbilical vein varix, it was later determined to be an extrahepatic persistent vitelline vein with an internal thrombus by postnatal ultrasound. It was successfully surgically excised. Conclusion: When an abnormal abdominal vascular structure near the umbilicus is found during prenatal ultrasonography, the persistent vitelline vein should be included in the differential diagnosis to allow prompt evaluation and treatment after birth.